Template-assisted polymeric spherules for the solid phase extraction of chlorfenapyr from contaminated water. Issue 3 (11th February 2021) - Abbas, Naseem; Hayat, Muhammad; Fatima, Hira; Manzoor, Sadia; Nawaz, Sana; Mabood, Fazal; Yasmean, Ghazala; Majeed, Abdul; Manzoor, Suryyia
ABSTRACT: This work presents a combination of three functional monomers, acrylonitrile, vinyl acetate, and acrylic acid to synthesize template assisted spherules for the selective recognition of chlorfenapyr; a halogenated pyrrole class of pro-pesticides. Chlorfenapyr imprinted polymer spherules (MIPs) were synthesized through precipitation polymerization, characterized, and applied to extract pesticide from agricultural run-off with an adsorption capacity of 8.7 mg/g. The imprinting effect was evaluated by comparing the binding ability of MIP to the structural analogues of chlorfenapyr. The maximum percentage recovery of 91%, limit of detection 3.5 × 10 −5  mol/L and limit of quantification 0.1 × 10 −4  mol/L were obtained.